Percutaneous mitral valve repair in patients developing severe mitral regurgitation early after an acute myocardial infarction: A review - Estévez-Loureiro, Rodrigo; Tavares Da Silva, Marta; Baz-Alonso, José Antonio; Caneiro-Queija, Berenice; Barreiro-Pérez, Manuel; Calvo-Iglesias, Francisco; González-Ferreiro, Rocio; Puga, Luis; Piñón, Miguel; Íñiguez-Romo, Andrés (Frontiers in Cardiovascular Medicine, 2022)
Acute mitral regurgitation (MR) may develop in the setting of an acute myocardial infarction (AMI) because of papillary muscle dysfunction or rupture. Severe acute MR in this scenario is a life-threatening complication associated with hemodynamic instability and pulmonary edema, and has been linked to a worse prognosis even after reperfusion. Patients treated solely with medical therapy have the highest mortality rates. Surgery has been the only treatment strategy until recently, but the results of the technique are hindered by high rates of morbidity and mortality. Therefore, the development of less invasive interventions for correcting MR would be ideal. We aimed to review the current role of transcatheter interventions in this clinical setting.